Classroom Arrangement in Nurul Islam Kindergarten to Support Student Creativity (Case Study: Nurul Islam Kindergarten, Surabaya) - Susanti, Wiwik Dwi; M. Safeyah; M. N. Trilita (Future Science)
The main problems in Nurul Islam Kindergarten Surabaya are related to the dimensions of classrooms and the availability of classrooms as a place to conduct sports activities. In the research trying to be able to provide a solution in optimizing available space resources so that it can be an accommodating container for learning activities. This is one of the factors that supports the success of the learning program. From the results of the analysis of observations in the field, the classrooms are arranged based on several zones so as to provide a solution for narrow classroom arrangement. The zone also functions to differentiate and limit the mixing of various types of activities. So that every activity can run smoothly.